Sonic theology : Hinduism and sacred sound - Beck, Guy L., 1948- (Studies in comparative religion (Columbia, S.C.), 1993)
Traditionally Hinduism has appealed to Western eyes though its rich tableau of visual artifacts: temple architecture, sculpture, painting, craft. Guy Beck argues, however, that the focus of Western scholars on Hinduism's visual component has often been at the expense of the religion's most important feature - its emphasis on sound. Beck addresses this longstanding imbalance in this pathbreaking study. He contends that sound possesses a central place in Hindu theory and practice and that Hinduism is essentially a sonic theology. Unlike religious traditions that emphasize silence, the Hindu world is permeated by sound. Drums, bells, gongs, cymbals, conches, flutes, and an array of vocalizations play a central role in the worship experience. Beck provides a theoretical exposition of the major textual sources of Hindu sacred sound, namely the Vedas, Upanishads, Mimamsa, Grammar, Yoga, Saiva-Agama, Sakta-Tantra, and Vaisnava Pancaratra. From the Vedic Vak as "spoken word" to the Sabda-Brahman of the Upanishads, Mimamsa, and Grammar, and on to the Nada-Brahman of Yoga, Saivism, Saktism, Vaisnavism, and Indian classical music, Beck argues that sound participates at every level of the Hindu cosmos. As he weaves the theology of sound throughout Hindu textual traditions, Beck provides ample, coherent justifications of the practical use of sound in Mantra repetitions, Om recitations, and Nada-Brahman meditational techniques. He compares the centrality of sound in Hindu theology to its role, or its absence, in other religions. The issues Beck raises about sound and language not only reshape our understanding of Hindu worship but also invite a fresh approach to comparative theology.